Aplikasi Akademik Untuk Pelayanan Wali Murid Berbasis SMS Gateway Pada SMP Negeri 2 Airgegas - Yudhi Rudini; Ari Amir Alkodri (ISB Atma Luhur, 2014)
During this very limited parents to monitor their children's academic activities ranging from school attendance, academic grades to violations committed by his son. That sometimes even surprise is when parents know their child's academic grades decreased and some are received letters of reprimand for their children's behavior. Thus the author makes an application for service-based SMS Gateway parents at SMP Negeri 2 Airgegas is expected able to assist parents in monitoring their learning activities at school, and help students to avoid reprimand the school due to absenteeism and decreased the value of their academic . Expected later this application can help the school, parents and students to improve student academic achievement in school